2015
DOI: 10.1039/c5tb00957j
|View full text |Cite
|
Sign up to set email alerts
|

Novel dendritic derivatives of unsaturated fatty acids as promising transdermal permeation enhancers for tenofovir

Abstract: This study was aimed at exploring the potential of unsaturated fatty acids (UFAs) [palmitoleic (PA), linoleic (LA), linolenic (LLA) and arachidonic acid (AA)], and their newly synthesized dendritic esters [PA1E, LA1E, LLA1E and AA1E] having basic tertiary nitrogen as the branching element as transdermal permeation enhancers for the delivery of tenofovir. The structures of the derivatives were confirmed by FTIR, NMR ( 1 H and 13 C) and HRMS. The in vitro cytotoxicity study revealed their biocompatibility. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…NEs were prepared by an ultra-sonication method ( 22 ) using mixtures of linolenic acid ester (LLA1E) ( 20 ) as the oily phase, Solutol HS 15 ® and PEG 400 as the surfactant/co-surfactant mixture (S mix ). The oily phase (LLA1E) and the S mix were mixed, the required quantity of milli-Q water was added and sonicated [probe Omni Sonic Ruptor 400 Ultrasonic Homogenizer (OMNI International, Kennesaw, GA, USA)] at 30% amplitude for 10 min (20°C) to form the blank NE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NEs were prepared by an ultra-sonication method ( 22 ) using mixtures of linolenic acid ester (LLA1E) ( 20 ) as the oily phase, Solutol HS 15 ® and PEG 400 as the surfactant/co-surfactant mixture (S mix ). The oily phase (LLA1E) and the S mix were mixed, the required quantity of milli-Q water was added and sonicated [probe Omni Sonic Ruptor 400 Ultrasonic Homogenizer (OMNI International, Kennesaw, GA, USA)] at 30% amplitude for 10 min (20°C) to form the blank NE.…”
Section: Methodsmentioning
confidence: 99%
“…Only a few local toxicity studies on transdermal skin effect ( 17 ) vaginal routes ( 18 , 19 ) and invitro studies ( 16 ) were reported. Tenofovir nanoparticles (NTDF) with novel dendritic properties have been developed by our team, invitro toxicity evaluation of the lipid component showed promising results ( 20 ). NTDF has potential to revolutionize the treatment of HIV infection through its effective penetration, reduction in administration frequency and effectiveness in attacking latent HIV virus in restricted areas in the body.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 The test material displaying percentage cell viability >70% can be considered as biologically safe and nontoxic to mammalian cells. 55 The biosafety of all ADs can be attributed to selection of non-toxic and biodegradable building blocks used for their synthesis.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…The optical density of each well was measured on a microplate spectrophotometer (Mindray MR-96A) at a wavelength of 540 nm. 39 The percentage cell viability was calculated as follows:…”
Section: Bacterial Cell Morphologymentioning
confidence: 99%